2020
DOI: 10.1039/d0na00635a
|View full text |Cite
|
Sign up to set email alerts
|

Production of Fe nanoparticles from γ-Fe2O3 by high-pressure hydrogen reduction

Abstract: In this work, the reduction of iron oxide γ-Fe2O3 nanoparticles by hydrogen at high pressures is studied. Increasing the hydrogen pressure enables reduction of γ-Fe2O3 to α-Fe at significantly lower...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…In this regard, a bigger effort may be put forth to develop an easy and scalable way to synthesize oxide precursors with high-quality nanocrystallites to preserve the nanoscale features before undergoing reduction [27,28]. Moreover, to make the process more efficient, different strategies have been proposed, such as the use of hydrogen at high pressure [29] or the application of a magnetic field during the reaction [30,31]. The latter was demonstrated to be highly efficient in terms of reduction of the processing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a bigger effort may be put forth to develop an easy and scalable way to synthesize oxide precursors with high-quality nanocrystallites to preserve the nanoscale features before undergoing reduction [27,28]. Moreover, to make the process more efficient, different strategies have been proposed, such as the use of hydrogen at high pressure [29] or the application of a magnetic field during the reaction [30,31]. The latter was demonstrated to be highly efficient in terms of reduction of the processing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…High phase-purity α ′′ -Fe 16 N 2 nanoparticles used in this study have been produced via a novel two-step route established by Dirba et al [23]. First, commercial γ-Fe 2 O 3 nanoparticles with an average particle size of 20-40 nm were reduced to α-Fe in high-pressure hydrogen [68]. In the second step, the resulting α-Fe nanoparticles were nitrogenated in an ammonia flow to produce the iron nitride.…”
Section: Methodsmentioning
confidence: 99%
“…Recent works have shown that nanocomposite magnets offer a possibility to engineer magnetic properties by using a mixture of hard and soft phases. , Therefore, in addition to improved densification, enhancing the maximum energy product (BH) max of ferrite magnets by increasing the saturation magnetization M s via the exchange-spring-magnet principle has been tried and, if successful, would have great technological and economical importance. For example, bulk composite magnets by using Al-doped Sr-hexaferrite SrAl 2 Fe 10 O 19 as the hard phase and environmentally friendly iron nitride α″-Fe 16 N 2 nanoparticles obtained by hydrogen reduction of Fe 2 O 3 as the soft (semihard) phase were studied demonstrating that indeed adding α″-Fe 16 N 2 leads to increased M s and a slight increase in M r …”
Section: Introductionmentioning
confidence: 99%